The United Nations World Water Development Report 2021 - United Nations Educational, Scientific; Cultural Organization (United Nations, 2021)
Water is a finite and non-substitutable resource. As the foundation of life, societies and economies, it carries multiple values and benefits. But unlike most other natural resources, it has proven extremely difficult to determine its true ‘value’. The 2021 edition of the United Nations World Water Development Report, titled “Valuing Water” assesses the current status of and challenges to the valuation of water across different sectors and perspectives and identifies ways in which valuation can be promoted as a tool to help improve its management and achieve global sustainable development.